PERANAN PRODUK AR-RUM DALAM PENGEMBANGAN USAHA MIKRO DAN KECIL PADA PEGADAIAN SYARIAH CABANG PANDAU PERMAI SIAK HULU KABUPATEN KAMPAR - Arfah, Arfah (Eko dan Bisnis: Riau Economic and Business Review, 2019)
Arrum products are one of the products owned by the Cabang Pegadaian SyariahÂ  Pekanbaru which is offered to micro and small entrepreneurs in the form of financing with the accompanying BPKB motorbike and car collateral in the form of fiduciary, the purpose of Pengadaian Syariah in issuing Arrum products is to help micro and small entrepreneurs who have runs at least one year in productive conditions that are lacking in capital in business development by providing loans or financing. The contract applied in arrum products is the financing contract with ijarah rates